Transsexualiteit : vreemdeling in eigen lichaam; juridische en medische opstellen - van der Reijt, F.A.; Pen, A.; Kirkels, V.G.H.J. (Zwolle : Tjeenk Willink, 1976)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie